Эпоксидные полимеры с 1 мас% нанокремнеземов различной удельной поверхности: прочность, химическая и термическая стойкость - Старокадомский, Д.Л.; Ткаченко, А.А.; Образков, А.Г.; Мошковская, Н.М.; Гаращенко, И.И.; Ищенко, А.А. (Вісник Українського матеріалознавчого товариства, 2017)
It is established that when introducing 1 wt. % nano silicas of different surface area - from 50 to 450 m² / g, the thermal parameters (according to the one-sided heating in air) and chemical resistance (for example, swelling in ether-acetate solvent) are increased. However, after filling there is no noticeable change in the investigated strength parameters.